Peran Pendidikan Kesiapsiagaan Bencana dalam Meningkatkan Kesadaran pada Remaja - Rahmi Fadiah Nasution; Evi Bunga Lestari; Usiono Usiono (Pusat Riset dan Inovasi Nasional, 2025)
Indonesia has a high level of disaster vulnerability, so community preparedness is necessary, especially among teenagers as the next generation. This study aims to analyze the role of disaster preparedness education in enhancing awareness and disaster mitigation skills among adolescents. Using qualitative methods through observation, interviews, and documentation, this research found that disaster preparedness education effectively enhances understanding and the active role of adolescents as agents of change. Although effective, challenges such as limited resources and lack of support are still faced. Therefore, cross-sector collaboration is necessary to ensure the sustainability of the program and significantly reduce disaster risk.